Direct regulation of the cardiac ryanodine receptor (RyR2) by O-GlcNAcylation - Chidinma A Okolo; Ei-Phyo Khaing; Valeria Mereacre; Rachel S Wallace; Michelle L Munro; Jeffrey R Erickson; Peter P. Jones (Cardiovascular Diabetology, 2023)
Abstract Background O-GlcNAcylation is the enzymatic addition of a sugar, O-linked β-N-Acetylglucosamine, to the serine and threonine residues of proteins, and is abundant in diabetic conditions. We have previously shown that O-GlcNAcylation can trigger arrhythmias by indirectly increasing pathological Ca2+ leak through the cardiac ryanodine receptor (RyR2) via Ca2+/calmodulin-dependent kinase II (CaMKII). However, RyR2 is well known to be directly regulated by other forms of serine and threonine modification, therefore, this study aimed to determine whether RyR2 is directly modified by O-GlcNAcylation and if this also alters the function of RyR2 and Ca2+ leak. Methods O-GlcNAcylation of RyR2 in diabetic human and animal hearts was determined using western blotting. O-GlcNAcylation of RyR2 was pharmacologically controlled and the propensity for Ca2+ leak was determined using single cell imaging. The site of O-GlcNAcylation within RyR2 was determined using site-directed mutagenesis of RyR2. Results We found that RyR2 is modified by O-GlcNAcylation in human, animal and HEK293 cell models. Under hyperglycaemic conditions O-GlcNAcylation was associated with an increase in Ca2+ leak through RyR2 which persisted after CaMKII inhibition. Conversion of serine-2808 to alanine prevented an O-GlcNAcylation induced increase in Ca2+ leak. Conclusions These data suggest that the function of RyR2 can be directly regulated by O-GlcNAcylation and requires the presence of serine-2808.